Does REDD+ Complement Law Enforcement? Evaluating Impacts of an Incipient Initiative in Madre de Dios, Peru - Montoya-Zumaeta, Javier G.; Wunder, Sven; Rojas, Eduardo; Duchelle, Amy E. (Frontiers in Forests and Global Change, 2022)
Subnational initiatives to Reduce Emissions from Deforestation and forest Degradation and enhance carbon stocks (REDD+) have been implemented across the tropics over the last decade. Such initiatives are often embedded within pre-existing conservation policies, such as forest law enforcement, making it challenging to disentangle attributable impacts. In this article, we analyze a new REDD+ project implemented in Brazil nut concessions in the southeastern Peruvian Amazon. Public law enforcement to verify compliance with Peru's Forest Law was already ongoing and intensified locally during our study period. Thus, we combine longitudinal data from remote sensing and household surveys of 197 concessionaires in a before–after control-intervention (BACI) study design to: a) evaluate the project's impacts during the 2012–2018 period on deforestation, forest degradation, and the participants' wellbeing and b) assess how the law-enforcing field inspections may have complemented the project effects. Our results show that the REDD+ initiative had insignificant effects on deforestation and forest degradation, but confirm the curbing effects of the field inspection measures on forest loss. The non-significance of the REDD+ effects may reflect delays in cash incentive payments to enrolled concessionaires, lack of careful alignment of benefit provision with project participants, and limited enforcement of project conditionalities. Most REDD+ participants reported a reduced subjective wellbeing, which may reflect the frustrated expectations associated with project implementation. We discuss the implications of our results and outline lessons for similar tropical forest conservation initiatives.